Deviations of Exchange Rates from Purchasing Power Parity : A Story Featuring Two Monetary Unions - MacDonald, Ronald (IMF Working Papers; Working Paper, 1998)
We examine the mean-reverting properties of real exchange rates, by comparing the unit root properties of a group of international real exchange rates with two groups of intra-national real exchange rates. Strikingly, we find that while the international real rates taken as a group appear mean-reverting, the intra-national rates are not. This is consistent with the view that while monetary shocks may be mean-reverting over the medium term, underlying real factors do generate long-term trends in real exchange rates.